2007
DOI: 10.1159/000098189
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the distribution of the telomeric sequence (T<sub>2</sub>AG<sub>3</sub>)<sub>n</sub> in the Macropodoidea (Marsupialia) by fluorescence in situ hybridization. II. The ancestral 2n = 22 macropodid karyotype

Abstract: In marsupial karyotypes with little heterochromatin, the telomeric sequence (T2AG3)n, is involved in chromosome rearrangements. Here we compare the distribution of the (T2AG3)n sequence in chromosomes recently derived by fusions and other rearrangements (7–0.5 MYBP) with its distribution in chromosomes derived earlier (24–9 MYBP). We have previously shown that the (T2AG3)n sequence is consistently retained during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
1
25
0
2
Order By: Relevance
“…G-banding and chromosome-painting studies suggest that metatherian chromosomes have been remarkably conservative with regard to large-scale rearrangements. More than 90% of the 211 metatherian species examined have diploid numbers between 14 and 22 (Hayman 1990; updated by Tyndale-Biscoe 2005) and chromosome morphology manifests only minor deviations between most species, the majority of which are easily explained by a few simple internal rearrangements and/or a small number of centromeric fissions and fusions (Rofe and Hayman 1985;Hayman 1990;Rens et al 2001Rens et al , 2003Ferreri et al 2004;Metcalfe et al 2007). Whether this strong karyotypic conservation is mirrored by parallel conservation in gene content and syntenic relationships has never been determined because of the sparseness of comparative gene mapping data from metatherian genomes.…”
Section: Chromosome Structure and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-banding and chromosome-painting studies suggest that metatherian chromosomes have been remarkably conservative with regard to large-scale rearrangements. More than 90% of the 211 metatherian species examined have diploid numbers between 14 and 22 (Hayman 1990; updated by Tyndale-Biscoe 2005) and chromosome morphology manifests only minor deviations between most species, the majority of which are easily explained by a few simple internal rearrangements and/or a small number of centromeric fissions and fusions (Rofe and Hayman 1985;Hayman 1990;Rens et al 2001Rens et al , 2003Ferreri et al 2004;Metcalfe et al 2007). Whether this strong karyotypic conservation is mirrored by parallel conservation in gene content and syntenic relationships has never been determined because of the sparseness of comparative gene mapping data from metatherian genomes.…”
Section: Chromosome Structure and Evolutionmentioning
confidence: 99%
“…With the opossum genome assembly in hand, and low-coverage sequencing of the wallaby genome well underway (http:// www.genome.gov/12512299), it will soon be possible to examine synteny relationships in fine detail in representatives of two very distinct and evolutionarily distant metatherian families. One reason this is so important is that chromosome painting studies have indicated that similar karyotypic structure in diverse metatherian families may reflect repeated reversals of chromosome fusions and fissions involving a small number of identical or very similar chromosomal breakpoints (Rens et al 2003; also see Metcalfe et al 2007). If so, the apparent structural conservation between the chromosomes of some groups of metatherians could be the result of character convergence rather than shared ancestry.…”
Section: Chromosome Structure and Evolutionmentioning
confidence: 99%
“…However, telomeric sequences can be localized not only at the terminal ends (true telomeres) but also at different interstitial sites of chromosomes (the so-called interstitial telomeric sequences or ITS) (Lee et al, 1993;Nanda et al, 2002;Metcalfe et al, 2007).…”
mentioning
confidence: 99%
“…Os sítios teloméricos intersticiais já foram considerados restos ancestrais de rearranjos cromossômicos produzidos durante a evolução do cariótipo em diferentes taxa Thomsen et al, 1996;Vermeesch et al, 1996; Fagundes e Yonenaga-Yassuda, 1998;Metcalfe et al, 2007;Pellegrino et al, 1999;Finato et al, 2000;Go et al, 2000). Rearranjos cromossômicos como inversões, translocações, fusões e fissões podem contribuir para a reorganização da arquitetura do genoma, oferecendo novas formas cromossômicas na qual a seleção natural pode atuar.…”
Section: Discussionunclassified
“…Sítios intersticiais teloméricos caracterizam-se como grandes blocos de DNA telomérico que se localizam principalmente em regiões centromérica e pericentromérica dos cromossomos (Meyne et al, 1990). Desde a primeira análise citogenética realizada por Meyne et al (1990) em 100 espécies de vertebrados, ITS foram localizados e descritos em vários mamíferos, como primatas do gênero Eulemur (Garagna et al, 1997;Go et al, 2000), roedores (Bertoni et al, 1996;Fagundes e Yonenaga-Yassuda, 1998;Castiglia et al, 2006, Ventura et al, 2006, marsupiais (Pagnozzi et al, 2000;Metcalfe et al, 2007), carnívoros (Wurster-Hill et al, 1989), cetartiodactyla (Scherthan, 1990Vermeesch et al, 1996), perissodactyla (Santani et al, 2002), quirópteros (Finato et al, 2000) bem como nos anfíbios (Wiley et al, 1992;Nanda et al, 2008), répteis (Schmid et al, 1994;Pellegrino et al, 1999), peixes (Abuín et al, 1996) e aves (Nanda et al, 2002).…”
Section: Methodsunclassified